Pentingnya guru dalam membangun fondasi pendidikan karakter - Munawir Munawir; Frida Dwi Rahayu; Davina Nafisah Salmah (Jurnal Pendidikan Dasar, 2025)
Character education is a fundamental aspect in shaping students' personalities and morals, encompassing not only cognitive domains but also affective and psychomotor aspects. Amid the challenges of globalization and rapid technological advancement, character education has become increasingly important in fostering a generation with integrity, responsibility, and strong human values. In this context, teachers play a highly strategic role as role models, facilitators, and motivators in instilling moral and ethical values in students. This research is conducted using a literature review approach to explore in depth how teachers contribute to building a foundation for character education through teaching methods, interpersonal approaches, and daily exemplary behavior. The findings indicate that teachers' contributions to the character education process are highly significant and should become a primary focus in the field of education, particularly in creating a learning environment that holistically supports students’ character development.Kata kunci: Character Education, Teacher's Role, Educational Foundation